Identification of acyl donors and acceptor proteins for fatty acid acylation in BHK cells infected with Semliki Forest virus. - Berger, M (1984)
The modification of viral glycoproteins through the covalent attachment of fatty acids was studied in baby hamster kidney (BHK) cells infected with Semliki Forest virus (SFV). Comparative pulse-chase experiments with [3H]palmitic acid and [35S]methionine revealed that a precursor polypeptide, designated p62, of the structural SFV glycoprotein and E1 serve as the primary acceptors of acyl chains. Acylation of p62 occurs immediately prior to its proteolytical cleavage to E2 and E3 emphasizing the post-translational and specific nature of this hydrophobic modification. To trace the acyl donor(s) for protein acylation the covalent attachment of fatty acids to p62 was studied after extremely short labeling periods with [3H]palmitic acid and correlated to the metabolism of the exogenous tritiated fatty acid. The shortest possible labeling time, a 10 s pulse with [3H]palmitic acid, was sufficient to acylate SFV p62. Analysis of the labeled lipids extracted from the same cells revealed that palmitoyl-CoA and phosphatidic acid showed the highest specific radioactivity among the tritiated lipid species. Out of these lipid species palmitoyl-CoA was identified as the functional acyl donor lipid in a cell-free system for the acylation of polypeptides.